Drain cover with filter / Suhaila Safie … [et al.] - Safie, Suhaila; Mohd Nor, Muhammad Fadzly; Shuib, Nurul Ain; Azmi, Nurul Amira Syahira; Sujali, Nurul Syafiqah; Abdul Raman, Noor Azah; Hussin, Juliyana; Abd Rahman, Mohd Fazli (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Malaysian construction industry has been through a reform especially in term of better-quality material technology fits the times. One of the materials that complement the infrastructure construction is a drain cover. The material that given more attention is cheaper but can work well and able to reduce more problems at a time. A product from a combined of drain cover from Fiber Reinforce Plastic (FRP) type material with a filter has been developed to reduce the problem of thief iron drain cover, clogged drain problems and at the same time able to ensure smooth flow of drain water and become more clear. Method of obtaining data is through experiment, interviews with those who involved in this industry and also questionnaires to the public or user. Result from an experimental analysis found that the products work very well to reduce the problem of clogged drains. In a nutshell, the combination of the FRP drain cover with filter more effective to reduce the thief of drain cover and clogged drain.